2019
DOI: 10.1590/0001-3765201920180654
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Clinical Isolates from a Southwest Brazilian Tertiary Hospital Exhibit MFS-mediated Azole Resistance Profile

Abstract: Candida albicans is the most frequent fungal species that causes infections in humans. Fluconazole is the main antifungal used to treat Candida infections, and its prolonged and indiscriminate use for the last decades are the most established causes which originated resistant strains. Fungal drug resistance is associated to alterations in ERG11 gene and overexpression of multidrug resistance (MDR) transporters belonging to two families: ATP-binding cassette (ABC) and Major Facilitator Superfamily (MFS). To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Due to the increasing resistance of Candida species associated with invasive infections and the potential of targeting sphingolipids, the present study aimed to test two inhibitors of sphingolipid synthesis, aureobasidin A and myriocin. Both drugs were evaluated against different Candida clinical isolates, including some that were described as strains that overexpress transmembrane transporters (ABC and MFS) related to multidrug resistance phenotype [ 24 , 25 ]. Aureobasidin A and myriocin inhibit inositolphosphorylceramide (IPC) synthase and glucosylceramide (GlcCer) synthase, respectively, which are two key enzymes for the synthesis of the most important sphingolipids found in fungi such as IPC and GlcCer.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing resistance of Candida species associated with invasive infections and the potential of targeting sphingolipids, the present study aimed to test two inhibitors of sphingolipid synthesis, aureobasidin A and myriocin. Both drugs were evaluated against different Candida clinical isolates, including some that were described as strains that overexpress transmembrane transporters (ABC and MFS) related to multidrug resistance phenotype [ 24 , 25 ]. Aureobasidin A and myriocin inhibit inositolphosphorylceramide (IPC) synthase and glucosylceramide (GlcCer) synthase, respectively, which are two key enzymes for the synthesis of the most important sphingolipids found in fungi such as IPC and GlcCer.…”
Section: Introductionmentioning
confidence: 99%
“…A clinical isolate of C. albicans , overexpressing CaMdr1 and CaCdr1 (strain 1114) [ 34 ] and the CgCdr1-overexpressing C. glabrata clinical isolate 109 [ 35 , 36 ], both obtained from patients at the University Hospital of Universidade Federal de Juiz de Fora, Minas Gerais, were used. The strains were identified by MALDI-TOF mass spectroscopy [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The capacity of the most active extracts to cause cells to accumulate the fluorescent cell-associated substrate of Mdr1 and Cdr1, Nile Red [ 41 – 43 ], was monitored by flow cytometry. Briefly, resistant and sensitive yeasts grown to exponential phase in SDB were centrifuged, washed two times with distilled water and kept on ice for 2 h [ 34 ]. Then, cells were incubated in 96-well microtitre plates (1 × 10 6 cells /well) containing SDB in the absence or presence of different concentrations of the extracts dissolved in DMSO at 30 °C for 2 h with shaking at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…A clinical isolate of C. albicans, overexpressing CaMdr1 and CaCdr1 (strain 1114) [34] and the CgCdr1overexpressing C. glabrata clinical isolate 109 [35,36], were used. Minimum inhibitory concentration (MIC) values, determined with an agar dilution assay as described below, revealed that strain 1114 was 515-times more resistant to FCZ than the sensitive strain C. albicans ATCC 90028 (MIC FCZ = 500 and 0.97 µg/mL, respectively) [37], whereas strain 109 displayed 64-fold more resistance to FCZ than C. glabrata ATCC 2001 (MIC FCZ = 1,000 and 15.6 µg/mL, respectively) [37].…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…The capacity of the most active extracts to cause cells to accumulate the uorescent cell-associated substrate of Mdr1 and Cdr1, Nile Red [41][42][43], was monitored by ow cytometry. Brie y, resistant and sensitive yeasts grown to exponential phase in SDB were centrifuged, washed two times with distilled water and kept on ice for 2 h [34]. Then, cells were incubated in 96-well culture plates (1 x 10 6 cells /well) containing SDB in the absence or presence of different concentrations of the extracts dissolved in DMSO at 30°C for 2 h with shaking at 200 rpm.…”
Section: Nile Red Accumulation Assaymentioning
confidence: 99%